Perencanaan Strategis Sistem Informasi Menggunakan Metode Ward & Peppard (Studi Kasus : CV. Berkah Rezki Solusindo) - Pindarko Hanung Widyantoro; Chris Rudianto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
CV. Berkah Rezki Solusindo is a company range in printing service. CV. Berkah Rezki Solusindo has several problems so that permormance becomes ineffective and inefficient. In the process of managing order data and raw materials it still uses the book recording method. The marketing process carried out by CV. Berkah Rezki Solusindo has also still used manual method, so that it has not attracted many customers. From the problem that exist in CV. Berkah Rezki Solusindo, the application of IS/IT can help the company’s business and marketing processes. CV. Berkah Rezki Solusindo can manage order data effectively and efficiently and can assist marketing activities by utilizing the internet in product promotion. To get an effective and efficient management information system, it is necessary to have good strategic planning. Therefore, research was carried out on strategic planning of information system using ward & pepard framework. In this study, several tools used for analysis were used, likely SWOT, Value Chain, CSF, and McFarlan Strategic Grid. Based on the result of the research, it make business strategies and IS/IT management strategies that use CV. Berkah Rezki Solusindo to develop human resources, markets, and product.